SOCIAL AND CLINICAL FACTORS ASSOCIATED WITH ORAL HEALTH RELATED QUALITY OF LIFE IN ELDERLY POPULATION IN IASI, ROMANIA - Alice Murariu; Carmen Stela Hanganu; Adina Armencia; Gabriela Geleţu; Livia Mihailovici (Romanian Society of Oral Rehabilitation, 2014)
Aim of the study To investigate the impact of oral health conditions and social factors on quality of life of older people in Iasi. Material and methods Data were collected from 336 subjects aged 65 to 74 years,175 addresed the dental office for treatment and 161 institutionalized in the Social Center "St. Parascheva". Oral healthrelated quality of life was assessed with the Geriatric Oral Health Assessment Index questionnaire. Results The risk for poor quality of life in terms of physical dimension was higher for females (OR=6.342) and for subjects who needed removable dentures (OR=5.043). In terms of oral discomfort the risk was higher for institutionalized (OR=6.329), and social limitation were correlated with female subjects (OR=3.899) and institutionalized subjects (OR=2.852). Conclusions Institutionalization can be considered as a factor with negative impacts on the quality of life of the elderly, affecting all the dimensions of the quality of life .